IMPROVING ENGLISH SPEAKING SKILLS TROUGH YOUTUBE - Siswanto, Siswanto (STIT Ibnu Rusyd Tanah Grogot, 2020)
The purpose of this study was to find out if the ability to speak English effectively by 8th grades at MTs Babussalam was improved by using YouTube. This paper focused on implementing YouTube as method for teaching speaking that is different, interesting, and fun, while creating a classroom atmosphere that is comfortable and increases, students’ enthusiasm for learning. This paper used the qualitative descriptive method as the method of research. The result of using YouTube was very effective because it followed students to speak with more confidence and expression. They also did not have to worry about the phrases they used when speaking because they were able to see how foreigners speak English properly and correctly